Al-Nasikh Wa Al-Mansukh(Description of Hadith Interpretation Methods) - rusita, rusita_sari; Hendra Ramadan (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to identify the nasikh and mansukh used by some hadith scholars when they have difficulty in combining two hadiths that collide and cannot be harmonized, and between which of the two hadiths is known to have arisen later. This result identifies the traditions of naskh can be done through tracing the clear statements of the Prophet, the words and explanations of the companions of the Prophet. know history, such as the hadeeth of Syaddad bin 'Aus and Ijma 'ulama'. And in terms of the model of naskh on the text (redaction and law), the substance of nasikh / mansukh applies in three circumstances; (1) the law of a redaction is deleted, but the redaction remains. (2) the redaction is deleted, but the ruling remains. (3) both the law and the redaction are deleted.